Mismatch between Anthropometics and Chair Dimension of Primary School Children (Level 1) In Northern Region, Malaysia - Md. Isa, Wahyuni Masyidah; Mohamed Khalid, Noor Azlina; Zainuddin , Muhammad Fauzi (Penerbit Universiti Sains Malaysia, 2013)
Several studies hav e been done on the issue of mismatch between the anthropometries dimension among school children and classroom furniture in different countries. All the studies shared the same results, showing that there is mismatch between the two variables (Mohd Azuan K. et al. 2010; Castellucci. Arezes &. Viviani 2009; NuruI Asyiqin el al. 2009; Lueder & Rice 2008; Gouvali & Boudolos 2006; Lipardo et al. 2006; Murphy, Buckle &. Stubbs 2003). The issue on mismatch in this paper does not only focus on chair dimension and anthropometric variables of the children, but it also investigates the possible negative implication of seating posture due to the mismatch (Castellucci, Arezes & Viviani 2009; Gouvali & Boudolos 2006; Parcells, Stommel & Hubbard 1999; Panagiotopoulou el al. 2004).